Teacher semiotic mediation and student meaning-making: A Peircean perspective (2014)
To interpret in detail the meaning-making in the classroom and the corresponding teacher semiotic mediation, we have resorted to Peirce¿s triadic sign theory, interpreted by Sáenz-Ludlow and Zellweger. We present an example of the use of a few elements of that theory in the analysis of a classroom episode in which meaning is constructed with the teacher¿s semiotic mediation.